Recent applications, future perspectives, and limitations of the CRISPR-Cas system - Sun-Ji Park; Ga Eun Lee; Soo Min Cho; Eui-Hwan Choi (Molecular Therapy: Nucleic Acids)
The CRISPR-Cas system has transformed our ability to edit and modify genomes in eukaryotic cells, offering unmatched precision and broad applicability. By utilizing a programmable RNA protein complex to introduce targeted double-strand breaks, the CRISPR-Cas system enables the correction of pathogenic mutations and the modulation of gene function with unprecedented efficiency. Its broad applicability spans the correction of inherited genetic defects through homology-directed repair to the disruption of deleterious alleles via non-homologous end joining. In this review, we first outline the molecular architecture and mechanistic basis of CRISPR-Cas9 and then consider its latest applications in modeling, drug screening, small-molecule-mediated editing, and treating hereditary, autoimmune, and oncological diseases. Emphasis is placed on the generation of disease-relevant cellular and animal models and on the potential of CRISPR-Cas9-mediated gene therapy to address hitherto intractable disorders. Finally, we discuss current challenges including off-target activity, gene editing efficiency, delivery constraints, and immunogenicity and highlight emerging strategies to overcome these hurdles and broaden the clinical impact of CRISPR-Cas systems.